EXPERIENCE OF IMMUNIZATION OF CHILDREN IN KRASNODAR KRAI WITH HEREDITARY HEMOLYTIC ANEMIAS - V. N. Firsova; A. V. Burlutskaia; E. V. Sharova (Кубанский научный медицинский вестник, 2017)
Aim. Study aspects of preventive treatment for infections in children with hereditary HA and analyze haemogram changes in immunization context.Materials and methods. There are 19 children with HA registered in Krasnodar, 26,31% of them are girls and 73,69% are boys. In 2015 – 2016 three children (two girls and one boy) with hereditary spherocytosis and ovalocytosis have been immunized in the Pediatric Child Care Department in Krasnodar Infectious Diseases Hospital.Results. Each child had scheduled immunizations. First day two children had fever at a febrile rate, headaches, apathy, decreased appetite. Hematologic tests showed increased symptoms of anemia and reticulocytosis. Billirubin chemistry value increased, mostly unconjugated. Fluid therapy, glucocorticosteroids, hepatoprotectors, spasmolytics, sorbents were prescribed to children, and it showed clinical improvement in patients condition, as well as laboratory test values normalization.Conclusion. Taking into consideration frequent infectious diseases in children with hereditary HA, it is reasonable to immunize them after splenectomy. Two children with hereditary HA were immunized while being in hospital and during the period of monitoring there were noticed deviations in hematological tests, but in a few days after immunization children’s condition was normal.Therefore it is reasonable to immunize children with hereditary HA in hospital, despite the possibilities of complications in the post immunization period.